La formación permanente del profesorado de Educación Física de Medellín. Una retórica que abandona entre la exclusión y la pobreza (2013)
ABSTRACT: The article reports the current situation of physi- cal education teachers in Medellin in relation to the constant training interpreted from the Human Development paradigm. This is a qualitative study using the historic-hermeneutic method; the information is collected through interviews, discussion groups, and documentary review. It establishes the existence of poverty in the physi- cal educator of Medellín related to their constant training as a social opportunity and transparency guarantees that influence their status as educator.